Research Trends in Parental Involvement in Elementary Reading Literacy: A Bibliometric Analysis - Tri Indah Sari; Sri Sukasih; Bambang Subali; Ellianawati Ellianawati (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
Parental involvement in reading literacy at elementary schools is crucial for fostering early literacy development, yet research trends on this topic remain fragmented. The gap lies in the lack of comprehensive mapping that identifies how parental roles are positioned within literacy interventions, particularly post-pandemic, as well as the underrepresentation of qualitative and longitudinal approaches. This study aims to map research trends on parental involvement in reading literacy at the elementary school level using a bibliometric approach. A total of 403 documents indexed in Crossref from 2021 to 2026 were retrieved using Publish or Perish and analyzed with VOSviewer to examine publication trends, source productivity, citation patterns, and keyword networks. The findings reveal a significant increase in publications in the post-pandemic period, indicating growing scholarly attention. However, parental involvement is still predominantly positioned as a supporting variable rather than a central agent, and qualitative and longitudinal studies remain underrepresented. Thematic shifts toward contextual factors such as engagement and family environment have not been accompanied by methodological diversification. In conclusion, this study highlights conceptual and methodological fragmentation and emphasizes the need for more holistic research, including qualitative, longitudinal, and cross-context approaches, as well as the exploration of parental digital literacy as a future research agenda.